2022
DOI: 10.1002/ncp.10928
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastrointestinal failure is associated with worse hemodynamic and perfusion parameters over 48 h after admission in patients with septic shock: Retrospective cohort study

Abstract: Background: This study aimed to investigate the relationship between acute gastrointestinal injury (AGI) and hemodynamic and perfusion parameters in the first week of intensive care unit (ICU) admission and evaluate the association of AGI with ICU and hospital outcomes in patients with septic shock undergoing mechanical ventilation.Methods: This retrospective cohort study applied the criteria proposed by the European Society of Intensive Medicine to classify the participants into risk/ dysfunction group (AGI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our results are consistent with previously published results by Sun et al, which showed that higher scores of AGI were associated with worse clinical variables, higher rates of septic shock, and higher 28 day mortality in a cohort of critically ill COVID-19 patients [47]. The relationship between AGI score and ICU outcome was studied by Klanovicz et al [52], who found that AGI III present within the first 48 h after ICU admission was a significant risk factor for ICU mortality in patients with septic shock undergoing mechanical ventilation. In septic and septic shock patients, AGI score on admission turns out to be a good 28 day survival predictive tool.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previously published results by Sun et al, which showed that higher scores of AGI were associated with worse clinical variables, higher rates of septic shock, and higher 28 day mortality in a cohort of critically ill COVID-19 patients [47]. The relationship between AGI score and ICU outcome was studied by Klanovicz et al [52], who found that AGI III present within the first 48 h after ICU admission was a significant risk factor for ICU mortality in patients with septic shock undergoing mechanical ventilation. In septic and septic shock patients, AGI score on admission turns out to be a good 28 day survival predictive tool.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, introducing luminal nutrients into critically ill patients with septic shock (receiving vasopressor) increases the risk of EFI and gastrointestinal dysfunction. Klanovicz et al [23] applied the European Society of Intensive Care Medicine's acute gastrointestinal injury (AGI) criteria to 163 mechanically ventilated patients with septic shock and found AGI was frequent during the first week of ICU admission. AGI risk/dysfunction was found in 87% and AGI failure in 12% and higher heart rate and lower mean arterial pressure were identified in patients with AGI failure [23].…”
Section: The Conundrum Of Introducing Luminal Nutrients In Septic Shockmentioning
confidence: 99%
“…Klanovicz et al [23] applied the European Society of Intensive Care Medicine's acute gastrointestinal injury (AGI) criteria to 163 mechanically ventilated patients with septic shock and found AGI was frequent during the first week of ICU admission. AGI risk/dysfunction was found in 87% and AGI failure in 12% and higher heart rate and lower mean arterial pressure were identified in patients with AGI failure [23]. In an analysis of more than 15 000 patients from an International Nutrition Survey, Heyland et al [24 & ] found that sepsis is associated with EFI (OR 1.34; 95% CI 1.17-1.54) and the daily mortality hazard ratio increased by a factor of 1.5 (95% CI 1.4-1.6; P < 0.0001) once EFI occurred.…”
Section: The Conundrum Of Introducing Luminal Nutrients In Septic Shockmentioning
confidence: 99%